Cretan refugees in Izmir : memory and identity - Hanyalı, Sümeyra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis examines the memory and identity of Cretan Muslims who were forced to migrate to Turkey after the Exchange of Population Convention between Greece and Turkey in 1923. After the signing of the convention, many people from Turkey and Greece became a refugee, and the Cretan Muslims in this context were both displaced and migrated to a place where they did not know the spoken language. Therefore, their adaptation process was much more difficult. The thesis attempts to analyze the collective memory of the forced migration experience and how Cretan refugees (mübadils) constructed their identities in the present. The oral narratives and life stories of Cretan Muslims who live in İzmir were used as primary sources in this thesis. Apart from oral narratives, it was also benefited from secondary sources and archival documents to present main framework of Cretan Muslims migration. Since there are not many resources on the migration experiences of Cretan Muslims, the main source of this thesis is the oral accounts.
Keywords: Muslims -- Crete(Greece) -- İzmir.; Crete(Greece) -- Turkey -- İzmir -- Identity.